Dosis de melaza de caña en el rendimiento del pollo de engorde Cobb 500, Zúngarococha Loreto - Garay Cahuachi, Andy Bruno (2025)
The research analysed the effect of different concentrations of honeydew on the diet of Cobb 500 broilers, highlighting its relevance as a supplement in poultry feed due to its potential benefits on feed efficiency and growth, crucial aspects for modern production. The main objective was to determine how five doses of cane molasses (0, 2, 3, 4 and 5 grams per liter) influence key variables such as final weight, weight gain, feed intake, feed conversion and feed efficiency. The study was designed with a completely randomized approach (DCA), applying five treatments and twenty replications for each. Data were collected weekly, and analyses of variance (ANOVA) and Tukey's tests allowed us to identify significant differences between treatments. The results showed that the dose of 5 g/liter of molasses generated the highest final weight and superior feed efficiency, significantly improving the productive performance of the chickens. Variability in feed conversion also indicated that molasses favors better efficiency in feed conversion into weight gain. Cane molasses, especially in high doses, positively impacts the performance of Cobb 500 chickens, improving weight gain and feed efficiency. The adoption of doses of 5 g/liter in poultry diets is suggested to maximize productivity and explore the application of molasses in different environmental and long-term contexts